Human Rights Education in Teacher Training Programs - MAKKAR, NEETU; Kaur, Ms. Gurminder (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Â Educated People are the greatest guarantee of Human Rights and, in effect serves as its ultimate sanction has fostered interest and efforts in the field of Human Rights Education. Human Rights Education means to make Human Rights universal and comprehensive by providing training in Human Rights and to aware people regarding Human Rights relating to life, liberty, equality and dignity of the individual. Recognition the universal concern about the contribution of Human Rights Education in ensuring the protection and realization of Human Rights, India has adopted multipronged strategy for ensuring Human Rights for its citizens. It incorporated into its constitution the various Human Rights as Fundamental Rights provided in the 1948 Universal Declaration of Human Rights (UDHR). Keeping in view the Ethnic diversity and highly divisive society of India, it has made provisions for the deprived sections of the society like the scheduled Castes (SC), Scheduled Tribes (ST) as well as girls and disabled persons. The present paper stresses that the Teacher Training Programs play a vital role in promoting Human Rights among the people. It aims to study that the Teachers are prepared through Pre-service and continuous In-service Teacher Education Programs that focused on Human Rights Education with in-depth knowledge about Human Rights, required teaching skills and practice of Human Rights in society.